Comparison of bit error rate performance for CDMA systems in different fading and AWGN channels - Ali Farzamnia; Muralindran Mariappan; Ramanan Thangasalvam; Ervin Moung (2018)
The DS-CDMA (Direct Sequence Code -CDMA (Slow Frequency Div Hopping CDMA), and MC-CDMA (Multi Carrier CDMA) are some of the very common and well known wireless communication techniques that is related to CDMA (Code Division for Multiple Access). Although these wireless techniques are well known, there is still a lack in research related to the performance analysis and comparison of the bit-error-rates (BER) of the wireless techniques with multiple number of users in the presence of fading channels. Thus, in this paper, the BER performance of DS-CDMA, SFH-CDMA and MC-CDMA wireless techniques in Rayleigh and Rician fading channels -users are presented, evaluated, and compared.